Financing Growth Analysis in BMT Al-Furqan Padang Sibusuk - Arwin, Arwin; Affandi, Faisal (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: This study aims to find out about the growth of financing for customers or members of BMT Al Furqan Padang Sibusuk in its role as a sharia microfinance institution to be a solution for small communities to get business capital and also to see the enthusiasm of the community in accessing financing for BMT Al Furqan Padang Sibusuk.Design/Method/Approach: This research is a semi-quantitative research, a combination of analysis carried out qualitatively and quantitatively, in which the nature of the categories is analyzed qualitatively, while the characteristic values to be used are numerical values that resemble quantitative analysis.Findings: After doing the research, it was found that the public's interest in getting access to financing at this microfinance institution was quite good, there was an increase in the amount of financing disbursed, and the amount of financing growth at BMT Al-Furqan Padang Sibusuk from the 2019 period and the 2020 period on financing products. Mudharabah and murabahah financing products experienced growth, namely the provision of mudharabah product financing in 2019 amounted to Rp.483.687.000 and grew in 2020 to Rp.529.228.000 (8,6 percent). Meanwhile, murabahah product financing in 2019 was Rp.892.839.000 rupiah and experienced growth in 2020 of Rp.1.537.940.000, - (41,1 percent). This microfinance institution has also provided many benefits, such as making it easier for members to get financing for business capital, especially micro and small businesses.Originality/Values: To obtain information about the development of financing carried out by BMT Al Furqan Padang Sibusuk, Sijunjung Regency, where this Islamic microfinance institution or BMT is not yet well known to the people of Sijunjung Regency.